2012
DOI: 10.1016/j.jmr.2012.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The design of a double-tuned two-port surface resonator and its application to in vivo Hydrogen- and Sodium-MRI

Abstract: The design and construction of a two-port surface transceiver resonator for both 1 H-and 23 Na-MRI in the rodent brain at 7T is described. Double-tuned resonators are required for accurately co-registering multi-nuclei data sets, especially when the time courses of 1 H and 23 Na signals are of interest as, for instance, when investigating the pathological progression of ischaemic stroke tissue in vivo. In the current study, a single-element two-port surface resonator was developed wherein both frequency compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
(72 reference statements)
2
11
0
Order By: Relevance
“…10 Recent studies involving human sodium MRI in the acute stroke period showed that sodium signal levels measured in the core tissue, defined by visibly increased DWI signal, remained normal up to 7 hours after arterial occlusion before eventually increasing. 8,9 This is consistent with the current and previous 13,17 rat stroke studies, where variable delay times were measured before TSC increased, coupled with early small decreases in sodium levels in the penumbra, suggesting that any increase above normal levels (we propose this as a viability threshold level) would indicate irreversible damage. In this case, permanent tissue damage would not be directly correlated with SOT, that is, the time of arterial occlusion, but rather the time at which sodium signal begins to increase above normal levels.…”
Section: Tissue Sodium Signal To Predict Stroke Onset Timesupporting
confidence: 89%
See 2 more Smart Citations
“…10 Recent studies involving human sodium MRI in the acute stroke period showed that sodium signal levels measured in the core tissue, defined by visibly increased DWI signal, remained normal up to 7 hours after arterial occlusion before eventually increasing. 8,9 This is consistent with the current and previous 13,17 rat stroke studies, where variable delay times were measured before TSC increased, coupled with early small decreases in sodium levels in the penumbra, suggesting that any increase above normal levels (we propose this as a viability threshold level) would indicate irreversible damage. In this case, permanent tissue damage would not be directly correlated with SOT, that is, the time of arterial occlusion, but rather the time at which sodium signal begins to increase above normal levels.…”
Section: Tissue Sodium Signal To Predict Stroke Onset Timesupporting
confidence: 89%
“…For quantitative measurements of the sodium signal, the mean signal in the core and penumbra was normalized to the mean sodium signal values measured in ROIs contralateral to the core and penumbra, respectively. Assuming a linear increase in the sodium signal in ischemic core tissue (as reported in previous studies 12,13,17 ), the signal in core ROI was fitted to a linear function according to Signal Na ðtÞ ¼ c þ s t where the line to which the sodium signal was fitted was characterized by the intercept c (the estimated sodium signal at SOT) and the rate of sodium signal change as a function of time s (the slope).…”
Section: Na and Apparent Diffusion Coefficient Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Of the alternative ways to receive different RF (radio frequency) signals from multiple‐nuclei from the same sample, the most widely explored are: multi‐tuned, switchable and individual isolated coils . Multi (dual)‐tuned coils use a common‐resonant conducting structure that resonates at multiple resonant frequencies . The common‐resonant structure used in these designs intrinsically suffers from moderate isolation between the receivers, which increases noise in the respective receivers.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of different approaches, including optimized coil designs [11,12], anatomic specific coil-designs [13], development of ultra short echo time sequences [14][15][16] and optimized radial sequence design [17], were suggested for enhancing the detectable 23 Na-MRI signal.…”
Section: Introductionmentioning
confidence: 99%